Evaluation of synthetic sex pheromone for monitoring and management of raspberry crown borer Pennisetia marginata (Lepidoptera: Sesiidae). (29th April 2013) - Teasdale, Carolyn; Judd, Gary J. R.; Gries, Regine; Gries, Gerhard
Abstract (E, Z)‐3, 13‐Octadecadienal (E3, Z13‐18:Ald) was recently identified as a sex pheromone component of the raspberry crown borer Pennisetia marginata (Harris) (Lepidoptera: Sesiidae). Although unstable, this pheromone may have utility for monitoring the seasonal abundance and flight phenology of adult P. marginata, as well as for developing control tactics, such as disorienting mate‐seeking males. Experiments conducted in raspberry and blackberry crops tested the effect of lure and trap attributes on captures of male P. marginata. Increasing lure loads (10, 100 or 1000 µg) of E3, Z13‐18:Ald significantly increased trap captures. Freshly prepared lures were significantly more attractive than lures aged for 2–10 days at room temperature. White wing traps and white delta traps were more effective than green delta or green bucket traps. Trap height in the crop canopy had no effect on the capture of males. When sex pheromone components of three other sesiid moth species were added to E3, Z13‐18:Ald, the attraction of male P. marginata was reduced and, thus, these components were identified as pheromone antagonists. Pheromone‐based mass trapping with 25 wing traps per hectare reduced captures of males in traps baited with a low‐dose (10 µg) pheromone lure by 67–87% in 2011.